LIVING CONSTITUTIONALISM’ AND THE ROLE OF INDIAN JUDICIARY - Mahalwar, Vandana (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Living Constitutionalism emerged as a popular theory of constitutional construction and interpretation. Living constitutionalism emerged as a reaction against Originalism. Originalism means that the text of the constitution has a set meaning and that constitutional actors should be bound by it. Originalists say that the text of any Constitution is fixed at the time it is drafted, hence, its interpretation should follow the original intention of the framers. While, the theory of Living Constitutionalism provides that constitution needs to be interpreted in consonance of the current socio-economic circumstances in a society. In the Constitution of India, the Indian Judiciary has played a crucial role by constructing its provisions in the interest of people of the nation. This article discusses the role of Indian judiciary in making the Constitution of India, a living document. It also discusses how the Indian judiciary has exhibited the demoprudence by expanding the ambit of Article 21 of the Constitution.